Peran Respon Emosional Dalam Memediasi Pengaruh Kualitas Produk Terhadap Pembelian Impulsif Konsumen Skincare - Ilfitriah, Aniek M; Adinugroho, Ferdiansyah (JIMF (Jurnal Ilmiah Manajemen Forkamma), 2026)
Abstract.This study examines the effect of product quality on impulse buying with emotional response as a mediating variable among MS GLOW skincare consumers. Using a quantitative approach, data were collected from 156 respondents through an online questionnaire and analyzed using Partial Least Square (PLS). The findings show that product quality has a positive and significant effect on impulse buying and emotional response.However, emotional response does not significantly influence impulse buying and does not mediate the relationship between product quality and impulse buying. These results indicate that impulse buying behavior among MS GLOW consumers is primarily driven by perceptions of product quality rather than emotional factors. The study highlights the importance of maintaining and improving product quality as a keymarketing strategy in the skincare industry.